WANPRESTASI TERHADAP PERJANJIAN PEMBIAYAAN INVESTASI DI BADAN USAHA MILIK DESA GERBANG LESTARI DESA DELUK KECAMATAN BANTAN KABUPATEN BENGKALIS (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Investment financing is the financing of capital goods and services needed for business / investment activities, rehabilitation, modernization, expansion, or relocation of business premises / investment provided to debtors. Investment financing done by Gerbang Lestari Village Owned Enterprises Deluk Village is to provide unsecured loans to customers who have become members of the Gerbang Lestari Village Owned Enterprises Deluk Village in accordance with the financing agreement made and agreed by the customer and the Owned Business Entity Desa Gerbang Lestari Desa Deluk. But in reality in the investment financing agreement the customers have defaulted. Defaults performed by customers that are late achievement, and defaults made by these customers are also contained in article 1238 of the Civil Code.The purpose of this study is to find out how the process of implementing investment financing agreements in the Village of Gerbang Lestari Village of Deluk Village and To find out how the settlement of defaults in the implementation of investment financing agreements in the Village of Gerbang Lestari Village of the Village of Deluk Village.Based on the results of the study of the causes of customers to default, that is, customers have failed in running their businesses, businesses run by customers are substandard, and indeed they lack the desire of customers to make loan repayment payments. In this case the State Owned Enterprises of the Gerbang Lestari Village Deluk Village makes it easy for customers to solve the problem of installment payments by providing relief to borrowers of investment financing to choose whether by making changes to the installment payment schedule or by changing the installment amount. However, if it is not implemented, the Gerbang Lestari Village of Deluk Village will take legal action by confiscating the assets of the customers whose economic value is equal to the number of loan installments that have not been paid. This is done in accordance with article 1131 of the Civil Code. It is recommended to the Entity-Owned Enterprise of Desa Gerbang Lestari Desa Deluk to be able to resolve the problem of default on investment financing made by the customer, because the investment financing loan funds come from community savings.Keywords: investment-credit financing without collateral-default